Four Inclinations in Human Nature: Evaluated in Light of Al-Ghazzâlî’s Concept of the Heart - Hatice P. Kemahlı (Spiritual Psychology and Counseling)
This article examines human nature and behavior through the lens of Al-Ghazzâlî’s concept of the heart (AR: qalb). The root of the Arabic word for heart means “turn, change.” A great thinker of Islamic civilization, Ghazzâlî held the heart as the spiritual center of man and that whatever occurs inside it manifests itself in the outside world. Therefore, a human being attempting to know himself must first observe the emotions and minute details in the inclinations of their heart. Ghazzâlî’s “heart” experiences continual change consequent to myriad forces from the physical (AR: jismânî) and the spiritual (AR: rûḥânî) worlds. Therefore, it is highly difficult to observe and understand this changeable spiritual organ. Ghazzâlî’s heart is the center of sentience and is home to a range of base instincts and inclinations, which Ghazzâlî terms the attributes of the heart, dividing them into four fundamental categories: animalistic/lust,2 predation/anger,3 divine,4 and satanic5 attributes. Ghazzâlî states that since these powers affect and change human nature and direct behavior, they can lead to degeneration.6 Likewise, they can potentially provide an opportunity for human development and safeguard one’s progeny when they are used as directed by the faculty of reason (AR: ͑aql).